Comparative Study between the 3D‐Liver Spheroid Models Developed from HepG2 and Immortalized Hepatocyte‐Like Cells with Primary Hepatic Stellate Coculture for Drug Metabolism Analysis and Anticancer Drug Screening. Issue 2 (14th December 2022) - Sae‐be, Arunsajee; Wiwatpanit, Teerawat; Varatthan, Thaveechai; Namporn, Thanaphon; Laungkulldej, Sasiwat; Thiabma, Ratthiya; Jaiboonma, Atchara; Sa‐ngiamsuntorn, Khanit; Elson, Daniel; Porter, Alexandra E.; Sathirakul, Korbtham; Hongeng, Suradej; et al.
Abstract: Liver spheroids may be the best alternative models for evaluating efficacy and toxicity of the new anticancer candidates and diagnostics for hepatocellular carcinoma (HCC). Here, novel 3D‐liver spheroid models are constructed from human hepatoma cells (HepG2)/ immortalized human hepatocyte‐like cells (imHCs) with primary hepatic stellate cells (HSCs) coculture using the ultralow attachment technique. Spheroid morphology, HSC distribution, metabolic activity, protein expressions, and drug penetration are evaluated. All developed 3D spheroid models exhibit in spherical shape with narrow size distribution, diameter between 639–743 (HepG2‐10%HSC) and 519–631 (imHC‐10%HSC) µm. Both imHC mono and coculture models significantly express normal liver biomarkers at the higher level than HepG2 models. While 3D‐HepG2 models significantly exhibit HCC biomarkers at the higher level than imHC models. HepG2 and imHC spheroids express basal cytochrom P450 (CYP450) enzymes at different levels depending on cell types, culture period, and ratio of coculture. Their metabolic activities for dextromethorphan (CYP2D6) tolbutamide (CYP2C9) and midazolam (CYP3A4) are routinely evaluated. For midazolam metabolism, imHC models allow the detection of phase II metabolic enzymes (UGT2B4 and UGT2B7). The presence of HSC in HepG2‐HSC model increases biological barrier for doxorubicin (DOX) penetration, and escalates IC50 of DOX from 61.4 to 127.2 µg mL −1 . Abstract : Novel 3D‐liver human spheroids constructed from HepG2 and immortalized hepatocyte‐like cells (imHC) with primary hepatic stellate coculture are compared for their morphology, metabolic activity, protein expression, and drug penetration. The imHC models significantly express normal liver biomarkers at higher levels than HepG2 models, while the HepG2 models express higher levels of hepatocellular carcinoma biomarkers than imHC models.